Counting the security cost of cheap calls. (November 2015) - German, Paul
Abstract : The decision to move to SIP trunking appears straightforward: reduced costs, greater scalability, improved disaster recovery options and access to the productivity benefits enabled by Unified Communications (UC). But, as ever in the world of technology, the truth about SIP trunking is a little more complex than it may appear at first glance. How much up-front investment is required to migrate from the existing ISDN trunk? How big is the hardware investment? How scalable is the solution? And, critically, is it secure? But is it secure? This issue is too often overlooked by companies wanting to move to SIP. The result is a ticking time bomb for businesses, with threats ranging from denial of service to toll fraud (also known as call jacking); and the liability lies squarely with the business, not the provider, as Paul German of VoipSec explains.